Association of Germline Variant Status with Therapy Response in High-risk Early-Stage Breast Cancer: A Secondary Analysis of the GeparOcto Randomized Clinical Trial - Pohl-Rescigno, Esther; Hauke, Jan; Loibl, Sibylle; Möbus, Volker; Denkert, Carsten; Fasching, Peter; Kayali, Mohamad; Ernst, Corinna; Weber-Lassalle, Nana; Hanusch, Claus; Tesch, Hans; Müller, Volkmar; et al. (JAMA Oncology, 2020)
Importance: The GeparOcto randomized clinical trial compared the efficacy of 2 neoadjuvant breast cancer (BC) treatment regimens: Sequential intense dose-dense epirubicin, paclitaxel, and cyclophosphamide (iddEPC) vs weekly paclitaxel and nonpegylated liposomal doxorubicin (PM) in patients with different biological BC subtypes. Patients with triple-negative BC (TNBC) randomized to the PM arm received additional carboplatin (PMCb). Overall, no difference in pathologic complete response (PCR) rates was observed between study arms. It remained elusive whether the germline variant status of BRCA1/2 and further BC predisposition genes are associated with treatment outcome. Objective: To determine treatment outcome for BC according to germline variant status. Design, Setting, and Participants: This retrospective biomarker study is a secondary analysis of the GeparOcto multicenter prospective randomized clinical trial conducted between December 2014 and June 2016. Genetic analyses assessing for variants in BRCA1/2 and 16 other BC predisposition genes in 914 of 945 women were performed at the Center for Familial Breast and Ovarian Cancer, Cologne, Germany, from August 2017 through December 2018. Main Outcomes and Measures: Proportion of patients who achieved PCR (ypT0/is ypN0 definition) after neoadjuvant treatment according to germline variant status. Results: In the study sample of 914 women with different BC subtypes with a mean (range) age at BC diagnosis of 48 (21-76) years, overall higher PCR rates were observed in patients with BRCA1/2 variants than in patients without (60.4% vs 46.7%; odds ratio [OR], 1.74; 95% CI, 1.13-2.68; P =.01); variants in non-BRCA1/2 BC predisposition genes were not associated with therapy response. Patients with TNBC with BRCA1/2 variants achieved highest PCR rates. In the TNBC subgroup, a positive BRCA1/2 variant status was associated with therapy response in both the PMCb arm (74.3% vs 47.0% without BRCA1/2 variant; OR, 3.26; 95% CI, 1.44-7.39; P =.005) and the iddEPC arm (64.7% vs 45.0%; OR, 2.24; 95% CI, 1.04-4.84; P =.04). A positive BRCA1/2 variant status was also associated with elevated PCR rates in patients with ERBB2-negative, hormone receptor-positive BC (31.8% vs 11.9%; OR, 3.44; 95% CI, 1.22-9.72; P =.02). Conclusions and Relevance: Effective chemotherapy for BRCA1/2-mutated TNBC is commonly suggested to be platinum based. With a PCR rate of 64.7%, iddEPC may also be effective in these patients, though further prospective studies are needed. The elevated PCR rate in BRCA1/2-mutated ERBB2-negative, hormone receptor-positive BC suggests that germline BRCA1/2 testing should be considered prior to treatment start. Trial Registration: ClinicalTrials.gov Identifier: NCT02125344.
CRIS-Team Scopus Importer:2020-03-27